Biochemical profile and survival in nonagenarians - Solichova, D; Melichar, B; Blaha, V; Klejna, M; Vavrova, J; Palicka, V; Zadak, Z (Clinical biochemistry, 2001)
OBJECTIVES: Old age is associated with an increase in frequency of disorders involving virtually all organ systems, resulting in a rise of mortality. The aim of the project was to study the relationship between biochemical markers and all-cause mortality in a defined age group. DESIGN AND METHODS: Thirty-eight nonagenarians, aged 92 +/- 2 (range 90-100) years entered the study. At the start of the study, a sample of peripheral blood and urine were obtained for analysis of 50 basic biochemical, hematologic and biologic parameters. The assessment was then repeated in 6 to 12 months intervals. The significance of difference between surviving subjects and those who died was examined by Mann-Whitney U test and the correlation between the variables was studied by Spearman rank correlation coefficient. RESULTS: During the observation period, 21 of the studied subjects died leaving 17 persons still alive at the end of the study. The mean time from the first measurement to the death was 12 +/- 10 (range 0-33) months. The mean follow-up time in surviving subjects was 31 +/- 12 (range 4-45) months. Serum vitamin E and calcium were significantly higher, and serum alanine aminotransferase (ALT) and urinary neopterin were significantly lower in survivors compared to the subjects who died. No other parameters were significantly different in survivors and in persons who died. Urinary neopterin exhibited a significant negative correlation with serum sodium concentration (RS = -0.50, p < 0.01), but the other parameters did not correlate significantly. CONCLUSION: In conclusion, among the parameters studied, differences between survivors and nonsurvivors were observed only for serum vitamin E, calcium, ALT and urinary neopterin. These findings may form a basis for prospective interventional trials in this group of patients.
Keywords: Oxidative Stress; mortalita; oxidační stres; Humans; Vitamin E; Immunity; Female; Aged; peroxidace lipidů; senioři; lidé; Antioxidants; Mortality; imunita; antioxidancia; ženské pohlaví; Male; Aged, 80 and over; senioři nad 80 let; mužské pohlaví; vitamin E; Lipid Peroxidation